2010
DOI: 10.1073/pnas.1002096107
|View full text |Cite
|
Sign up to set email alerts
|

National housing and impervious surface scenarios for integrated climate impact assessments

Abstract: Understanding the impacts of climate change on people and the environment requires an understanding of the dynamics of both climate and land use/land cover changes. A range of future climate scenarios is available for the conterminous United States that have been developed based on widely used international greenhouse gas emissions storylines. Climate scenarios derived from these emissions storylines have not been matched with logically consistent land use/cover maps for the United States. This gap is a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
157
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(157 citation statements)
references
References 23 publications
0
157
0
Order By: Relevance
“…Across the United States, disproportionate land use changes are expected to continue to occur on grasslands and shrublands for multiple future scenarios (Bierwagen et al 2010). Mirroring this pattern, in the Central Valley, more than half of the land area is predicted to change by 2051 (Radeloff et al 2012), with an increase in irrigated pasture and urban lands and a decrease in rangelands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the United States, disproportionate land use changes are expected to continue to occur on grasslands and shrublands for multiple future scenarios (Bierwagen et al 2010). Mirroring this pattern, in the Central Valley, more than half of the land area is predicted to change by 2051 (Radeloff et al 2012), with an increase in irrigated pasture and urban lands and a decrease in rangelands.…”
Section: Introductionmentioning
confidence: 99%
“…These storylines can serve as the basis for developing an integrated narrative of both climate and LULC change, and their combined impacts to a suite of biological resources and ecosystem services. Few studies have examined the combined effects of climate and land use change (de Chazal and Rounsevell 2009;Bierwagen et al 2010). One example is a California study that found that for many bird populations, the potential impacts of development can be as great as or greater than the effects of climate change, and threats may vary in different combinations across the landscape (Jongsomjit et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their consistency with the climate scenarios and information was one of the factors that supported their use. The scenarios present information on housing density and impervious surface cover that are consistent with the SRES storylines (Bierwagen et al 2010). …”
Section: Reflections and Issues For Evaluation And Planningmentioning
confidence: 99%
“…Road, roof, and parking surfaces within urban areas have been shown to lead to increased speed and volume of stormwater runoff and lower groundwater recharge (Erickson and Stefan 2009). In a nationwide assessment, the large increase in population and assumption of dispersed development under the A2 scenario results in about 10 percent increase in the surface area of impervious surfaces compared to the B1 storyline, and at least one-third of the nation's wetlands will be affected by 2050 in both scenarios (Bierwagen et al 2010). Urban planning to date has done relatively little to try to mitigate these effects, and by extension our A2 scenario might continue to produce them, especially since the urban footprint would expand under a "business as usual" storyline.…”
Section: Potential Impact Of Urbanization On Microenvironmental Condimentioning
confidence: 99%